THE IMPORTANCE OF GOOD ADHERENCE TO METHOTREXATE IN THE TREATMENT OF RHEUMATOID ARTHRITIS - Ceranic, Jelena; Kisic Tepavcevic, Darija; Ristic, Gorica (Medicinski podmladak, 2024)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by symmetrical peripheral polyarthritis and progressive joint damage. Disease-modifying antirheumatic drugs (DMARDs) reduce disease activity, and radiological progression of the joints, and improve the long-term functional status of patients with RA. The precondition for these positive outcomes is adequate patient adherence to DMARDs. According to the latest EULAR (The European Alliance of Associations for Rheumatology) recommendations, methotrexate (MTX) is still the first-line drug for the treatment of RA. It is characterized by safety and effectiveness, different ways of administration, the possibility of dose titration, as well as low treatment costs. It can be used as monotherapy or in combination with other synthetic or biological DMARDs. Methotrexate is an antimetabolite, a structural analog of folic acid, which inhibits the de novo synthesis of purines and pyrimidines, necessary for the synthesis of DNA and RNA, but acts on inflammation and other mechanisms such as increased release of adenosine, inhibition of the transmethylation reaction, reduced accumulation of polyamines and separation of nitric oxide synthase. Methotrexate affects the function of almost all cell types involved in inflammation (neutrophils, monocytes, T and B cells, endothelial cells, and fibroblast-like synovium). However, not all patients respond well to MTX, which can partly be explained by non-adherence. Optimal use of MTX involves starting therapy without delay, following the recommended dose and regimen until a satisfactory response to therapy is achieved, and following the maintenance dose. More than 200 variables influencing adherence have been identified, but none of these variables have been consistently linked in all previous research. Therefore, it is not possible to create a specific risk profile for non-adherence. Considering this fact and the existence of a significant number of non-adherent patients, there is a need to find tailored interventions to improve adherence to MTX in patients with RA that could improve the final outcomes of the disease.
Keywords: rheumatoid arthritis; adherence; methotrexate; treatment